A Case of a Vitreomacular Traction-Associated Macular Microhole in an Eye with Focal Choroidal Excavation - Fukumoto, Masanori (Case Rep Ophthalmol, 2015)
PURPOSE: It was the aim of this study to report a case of a vitreomacular traction-associated macular microhole (MMH) in an eye with focal choroidal excavation (FCE) detected by spectral-domain optical coherence tomography (SD-OCT). PATIENTS AND METHODS: A 38-year-old Japanese female presented to our clinic complaining of metamorphopsia in her left eye. The patient then underwent SD-OCT as well as a routine ophthalmological examination. She had a previous history of a macular hole in her right eye that had been successfully treated by pars plana vitrectomy. RESULTS: Upon initial examination, her best-corrected visual acuity was 20/25 in the left eye with a refractive error of −10.25 diopters. Examination by SD-OCT revealed an MMH with an outer retinal defect adjacent to the FCE. SD-OCT also revealed an intraretinal cystoid space in the macula with vitreous attachment around the foveal center. CONCLUSIONS: The findings of this report show that variable changes are likely to be associated with FCE. However, the etiology of FCE has yet to be fully elucidated and careful observation is necessary in cases of FCE.